Sindh Social Protection Policy Note - World Bank (World Bank, Washington, DC, 2019)
The 18th Amendment to the Constitution of Pakistan shifted the administrative paradigm from centralized to decentralized structures. The added obligations require major policy and institutional reforms in an otherwise weak social protection (SP) sector at provincial levels, generally characterized by limited planning, coordination, execution, and monitoring capacities. SP has become a salient feature of social policy, nationally as well as internationally. The basic components of a SP framework include safety nets or social assistance, social care for children and the elderly, social insurance and labor market interventions for productive employment generation. SP is conferred as an entitlement in the Pakistani Constitution, and the Government of Sindh (GoS) has demonstrated political commitments to this. This note outlines the key considerations of a policy on SP as part of the GoS commitment to reduce poverty, inequality, and vulnerability in the province. Section one gives introduction. Some of the key development challenges that a SP policy may need to consider prioritizing is described in section two. Sections three and four describes critical design principles of SP policies and programs, respectively. Section five reviews the current de facto SP programming in Sindh, while section six delineates a way forward for policy development.